Mechanical Stress Induces Sodium Entry and Osmoprotective Responses in Murine Synovial Fibroblasts - Proff, Annemarie; Nazet, Ute; Schröder, Agnes; Jantsch, Jonathan (Cells (Basel, Switzerland), 2024)
Osteoarthritis (OA) is a multifactorial disease depending on molecular, genetic, and environmental factors like mechanical strain. Next to the cartilage and the subchondral bone, OA also affects the synovium, which is critically involved in the maintenance of joint homeostasis. As there is a correlation between the extracellular sodium content in the knee joint and OA, this study investigates the impact of sodium on OA-associated processes like inflammation and bone remodeling without and with mechanical loading in synovial fibroblasts. For that purpose, murine synovial fibroblasts from the knee joint were exposed to three different extracellular sodium chloride concentrations (−20 mM, ±0 mM and +50 mM NaCl) in the absence or presence of compressive or intermittent tensile strain. In addition to the intracellular Na+ content and gene expression of the osmoprotective transcription factor nuclear factor of activated T cells 5 (Nfat5), the gene and protein expression of inflammatory mediators (interleukin-6 (IL6), prostaglandin endoperoxide synthase-2 (Ptgs2)/prostaglandin E2 (PGE2)), and factors involved in bone metabolism (receptor activator of NF-κB ligand (RANKL), osteoprotegerin (OPG)) were analyzed by qPCR and ELISA. Mechanical strain already increased intracellular Na+ and Nfat5 gene expression at standard salt conditions to levels obtained by exposure to increased extracellular Na+ content. Both high salt and compressive strain resulted in elevated IL6 and PGE2 release. Intermittent tensile strain did not increase Il6 mRNA expression or IL6 protein secretion but triggered Ptgs2 expression and PGE2 production. Increased extracellular Na+ levels and compressive strain increased RANKL expression. In contrast, intermittent tension suppressed RANKL expression without this response being subject to modification by extracellular sodium availability. OPG expression was only induced by compressive strain. Changes in extracellular Na+ levels modified the inflammatory response and altered the expression of mediators involved in bone metabolism in cells exposed to mechanical strain. These findings indicate that Na+ balance and Nfat5 are important players in synovial fibroblast responses to mechanical stress. The integration of Na+ and Na+-dependent signaling will help to improve the understanding of the pathogenesis of osteoarthritis and could lead to the establishment of new therapeutic targets.